Proton and phosphorus magnetic resonance spectroscopy of the healthy human breast at 7 T - van der Kemp, Wybe J.M. (NMR Biomed, 2016)
In vivo water‐ and fat‐suppressed (1)H magnetic resonance spectroscopy (MRS) and (31)P magnetic resonance adiabatic multi‐echo spectroscopic imaging were performed at 7 T in duplicate in healthy fibroglandular breast tissue of a group of eight volunteers. The transverse relaxation times of (31)P metabolites were determined, and the reproducibility of (1)H and (31)P MRS was investigated. The transverse relaxation times for phosphoethanolamine (PE) and phosphocholine (PC) were fitted bi‐exponentially, with an added short T (2) component of 20 ms for adenosine monophosphate, resulting in values of 199 ± 8 and 239 ± 14 ms, respectively. The transverse relaxation time for glycerophosphocholine (GPC) was also fitted bi‐exponentially, with an added short T (2) component of 20 ms for glycerophosphatidylethanolamine, which resonates at a similar frequency, resulting in a value of 177 ± 6 ms. Transverse relaxation times for inorganic phosphate, γ‐ATP and glycerophosphatidylcholine mobile phospholipid were fitted mono‐exponentially, resulting in values of 180 ± 4, 19 ± 3 and 20 ± 4 ms, respectively. Coefficients of variation for the duplicate determinations of (1)H total choline (tChol) and the (31)P metabolites were calculated for the group of volunteers. The reproducibility of inorganic phosphate, the sum of phosphomonoesters and the sum of phosphodiesters with (31)P MRS imaging was superior to the reproducibility of (1)H MRS for tChol. (1)H and (31)P data were combined to calculate estimates of the absolute concentrations of PC, GPC and PE in healthy fibroglandular tissue, resulting in upper limits of 0.1, 0.1 and 0.2 mmol/kg of tissue, respectively.